A mentoring model for student teachers in inclusive schools - Custodio, Zhanina Umali (College of Education, University of the Philippines Diliman, 2019)
The study revealed a mismatch in the conceptualization and practice of inclusive education where mentors inadvertently limit the participation and achievement of LDGTL. Mentors were also found to be unequipped in handling inclusion in the regular classroom and this was evidenced by the inefficiency of their mentees, thus, mentoring was not enough to prepare student teachers for inclusion. The developed internship model was recommended as baseline information for policy makers and education leaders in strengthening the capacity of both pre-service and in-service teachers towards the implementation of inclusive education.